Organic Cage Dumbbells. Issue 17 (3rd March 2020) - Greenaway, Rebecca L.; Santolini, Valentina; Szczypiński, Filip T.; Bennison, Michael J.; Little, Marc A.; Marsh, Andrew; Jelfs, Kim E.; Cooper, Andrew I.
Abstract: Molecular dumbbells with organic cage capping units were synthesised via a multi‐component imine condensation between a tri‐topic amine and di‐ and tetra‐topic aldehydes. This is an example of self‐sorting, which can be rationalised by computational modelling. Abstract : Linking cages : Molecular dumbbells with organic cage capping units were synthesised via a multi‐component imine condensation between a tri‐topic amine and di‐ and tetra‐topic aldehydes. This is an example of self‐sorting, which can be rationalised by computational modelling.